Laurence Housman's "The Moon-Flower" and Victorian mystic imagination - Wieliczko-Paprota, Emilia (Adam Mickiewicz University, 2018)
The paper explores the theme of mysticism in Laurence Housman’s fairy tale “The Moon-Flower” (1895). It presents the main assumptions of a Victorian inner journey toward a mystical union and analyses symbols which construct the inner landscape which undergoes a mystic transformation. The author attempts to show the metamorphosis of the fairy tale’s main characters and identify its roots in both fairy tale and religious traditions. It is argued that Victorian fairy tales reflect a credible quintessence of the universe. The retold tales of an archetypical quest full of powerful symbols uncover the sublime world hidden under the dull reality. Hence, “The Moon-Flower” is believed to tell the story of inner transformation and open the doors to the myriad stories which were told before and create countless possibilities of interpretation.
Keywords: mysticism; fairy tale; Victorian mystical imagination; archetypical symbol; inner landscape